A New Direction-Finding System for Auroral Hiss in Antarctica Besed on the Measurement of Time Difference of Wave Arrival at Three Spaced Observing Points - Nishino, Masanori; Tanaka, Yoshihito; Iwai, Akira; Yamaguchi, Toshiaki; Kamada, Tetsuo; Hirasawa, Takeo (1981)
P(論文) A newly developed direction finding ("DF") for auroral hiss based on the measurement of time difference of wave arrival was carried out in 1978 at Syowa Station (geomag. lat. -70.4°), Antarctica and its two slave unmanned observing points located at about 20km from Syowa Station. The auroral hiss signals received at the two spaced points were transmitted to Syowa Station by 2GHz telemeters. The arrival time difference of auroral hiss between Syowa Station and each spaced point was automatically determined by cross-correlating the waveforms of the received signals. It has been found that the new DF can determine localized exit regions at the ionospheric level which show a rapid temporal movement. A comparison of the DF results with ground-based auroral data has shown that impulsive type auroral hiss with a wide frequency range larger than several tens kHz has not emerged from the whole region of bright aurora but from some localized regions of bright auroras at the ionospheric level, and that the arrival directions of auroral hiss change rapidly in accordance with the auroral movements. The time resolution of the new DF is about 3μs by the measurement of delay times between two observing points in the reception of NAA wave. Therefore, the incident and azimuthal angles were measured with an accuracy of about 10°in the range of incident angle of 20°to 80°. departmental bulletin paper